Vitamin D status and endothelial function - Alyami, Ali Mahdi M (Curtin University, 2017)
Inadequate Vitamin D status is observed throughout the world. Endothelial dysfunction is central to the process of cardiovascular disease and Type 2 diabetes, whose global prevalence has significantly increased. In this thesis I have examined the interrelationships of vitamin D status, endothelial dysfunction, systemic inflammation and dyslipidaemia to shed more light on this important area. This has been accomplished through cross sectional clinical trials and a systemic review and meta-analysis of current evidence.